The clinical display of radiologic information as an interactive multimedia report...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Maloney K; Hamlet CT (Journal of Digital Imaging)
We regard the delivery of radiological information as an interactive multimedia report. We use a multimedia report model based on Extensible Markup Language (XML), rather than a traditional workstation model. Others have suggested a similar document-based approach. This display presentation includes image-related and text-based information and may contain interactive components (e.g., window, level and zoom). Using XML as a foundation for this multimedia presentation, we achieve flexibility and platform independence at a lower cost. XML allows for the separation of content and form. Content information, defined as elements (e.g., images, radiologic reports, and demographic information), is treated as independent information objects. The behavior of the elements can be changed for different users and tasks. In addition, by separating format detail from content, the appearance of the elements within the report can be modified. XML does not replace existing standards (i.e., Digital Imaging and Communications in Medicine [DICOM], Transmission Control Protocol/Internet Protocol [TCP/IP]). Instead, it provides a powerful framework that is used in combination with existing standards to allow system designers to modify display characteristics based on user need. We describe our application of XML to the clinical display of radiologic information. Copyright (c) 1999 by W.B. Saunders Company